Evaluation of the neoplastic infiltration of the skin overlying canine subcutaneous soft tissue sarcomas: An explorative study. (18th January 2021) - Del Magno, Sara; Morello, Emanuela; Iussich, Selina; Gola, Cecilia; Dalpozzo, Boris; Annoni, Maurizio; Martano, Marina; Massari, Federico; Giacobino, Davide; Piras, Lisa Adele; Stefanello, Damiano; Buracco, Paolo
Abstract: Studies regarding the neoplastic infiltration of the skin overlying canine subcutaneous soft tissue sarcoma (sSTS) are lacking. In case of the absence of tumor infiltration, there would be the possibility of leaving this unaffected skin in place, thus simplifying surgery. The aim of the study was to investigate whether the skin overlying sSTSs is infiltrated by neoplastic cells. Dogs with sSTSs treated surgically were prospectively enrolled. After excision, the skin was dissected from the tumor along the natural surgical plane of cleavage and histologically evaluated. Twenty‐nine dogs with an sSTS were included (22 grade I, 6 grade II, and 1 grade III). The sSTS‐overlying skin was not tumor‐infiltrated in 14/29 cases (48.3%). A higher frequency of infiltration was observed in higher grade sSTSs (grades II and III, 100%; P  = .006); nevertheless, 8/22 grade I sSTSs (36%) also showed cutaneous infiltration. This infiltration involved the dermis of the skin directly in contact with the tumor (multifocal in 11 and diffuse in four cases). Although the cutaneous tumor infiltration is less frequent in grade I sSTSs and a wide excision may still be the safest treatment for any sSTS for a greater possibility of local control, this study opens the possibility to a less aggressive cutaneous excision, but still with a local curative intent, as only the skin directly in contact with the sSTS has been proven to be tumor‐infiltrated. Additional studies are warranted to confirm that excision of only this skin may guarantee a complete local control, especially in lower‐grade sSTSs.